2011
DOI: 10.1073/pnas.1102664108
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific characterization of threonine, serine, and tyrosine glycosylations of amyloid precursor protein/amyloid β-peptides in human cerebrospinal fluid

Abstract: The proteolytic processing of human amyloid precursor protein (APP) into shorter aggregating amyloid β (Aβ)-peptides, e.g., Aβ1-42, is considered a critical step in the pathogenesis of Alzheimer's disease (AD). Although APP is a well-known membrane glycoprotein carrying both N-and O-glycans, nothing is known about the occurrence of released APP/Aβ glycopeptides in cerebrospinal fluid (CSF). We used the 6E10 antibody and immunopurified Aβ peptides and glycopeptides from CSF samples and then liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
217
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(226 citation statements)
references
References 47 publications
4
217
0
5
Order By: Relevance
“…No other glycoforms were observed. Further glycosylation of Tyr-681 and the tryptic peptide Thr-652, Thr-659, and Thr-663 had previously been identified on sAPP in cerebrospinal fluid (52). Similar studies showed an identical glycan structure of Thr-651 using media from SorLA-DDD-transfected cells, but we were unable to detect other glycosylated peptides (data not shown).…”
Section: Volume 290 • Number 6 • February 6 2015supporting
confidence: 43%
“…No other glycoforms were observed. Further glycosylation of Tyr-681 and the tryptic peptide Thr-652, Thr-659, and Thr-663 had previously been identified on sAPP in cerebrospinal fluid (52). Similar studies showed an identical glycan structure of Thr-651 using media from SorLA-DDD-transfected cells, but we were unable to detect other glycosylated peptides (data not shown).…”
Section: Volume 290 • Number 6 • February 6 2015supporting
confidence: 43%
“…Thus, the main purpose of the ECD experiments was to determine the amino acid attachment sites of O-linked glycans. Traditionally, O-linked glycans are attached to serine or threonine residues but recently we reported a tyrosine residue to be modified by a sialylated O-linked glycan on amyloid beta peptides in human cerebrospinal fluid (59). However, our ECD…”
mentioning
confidence: 54%
“…For example, lipolysis-stimulated lipoprotein receptor was newly identified in this study as a GalNAc-O-glycoprotein, and even though stimulated lipoprotein receptor was found in lysates of Capan-1 and COLO-205 as well as in secretomes of all three cell lines, the secretomes contributed to the identification of almost all the O-glycosites observed. In addition, peptides found exclusively in the secretomes of COLO-205 and K562 pointed to several new O-glycosites not previously identified in studies of amyloid ␤ A4 precursor (APP) (see "Discussion") (4,28,29).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we also found these peptides and identified glycoforms bearing up to five of the six available sites. This region of APP has been identified in two previous MS-based studies, as recombinant human isoform APP695 secreted from CHO cells (28), and in the form of short APP/A␤ glycopeptides immunoprecipitated from human cerebrospinal fluid (4). In neither of these studies were more than three sites within the 649 -670 segment unambiguously identified.…”
Section: Stshegleedkdhpttstlmentioning
confidence: 88%
See 1 more Smart Citation